Front Cover: Photoactivatable Mussel‐Based Underwater Adhesive Proteins by an Expanded Genetic Code (ChemBioChem 18/2017). (1st September 2017) - Hauf, Matthias; Richter, Florian; Schneider, Tobias; Faidt, Thomas; Martins, Berta M.; Baumann, Tobias; Durkin, Patrick; Dobbek, Holger; Jacobs, Karin; Möglich, Andreas; Budisa, Nediljko
Abstract : The cover picture shows a new concept for producing DOPA‐rich underwater adhesive proteins from marine mussels by genetic code expansion. By using computational design and genetic selection methods, a novel Methanocaldococcus jannaschii tyrosyl‐tRNA synthetase‐based enzyme was engineered. It activates the photocaged DOPA derivative ortho ‐nitrobenzyl (ONB)‐DOPA for incorporation into proteins in response to amber stop codons through orthogonal translation. In this way, mussel proteins are equipped with ONB‐DOPA at multiple sites, and this introduces spatiotemporal control over their adhesive properties. Exposure to UV light triggers cleavage of the ONB photocage, liberating the adhesive catechol side chain of DOPA. This strategy provides new ways for producing DOPA‐based wet adhesives for application in industry and biomedicine. More information can be found in the communication by N. Budisa et al. onpage 1819 in Issue 18, 2017 (DOI:10.1002/cbic.201700327 ).